Streamer Attractiveness, Information Quality, Cognitive Assimilation of Live Streaming Impulsive Buying: Millennial and Z Moderation - Guruh Ghifar Zalzalah; Fitriana Nur Samsiah (Telaah Bisnis, 2026)
This research aims to study the influence of streamer attractiveness, information quality, and cognitive assimilation on impulse purchases in live streaming shopping differences between millennials and generation z as moderating variables. This research uses the SOR (Stimulus-Organism-Response) theory. This research was conducted around the island of Indonesia in 2025, the sample used was 250 respondents. The sampling technique used purposive sampling method. The data analysis technique in this study uses Partial Least Squares Structural Equiation Modeling (SEM-PLS) using the help of WarpPLS software version 7.0. The results of this study indicate that streamer attractiveness, and information quality have a positive and significant effect on cognitive assimilation, cognitive assimilation has a positive and significant effect on impulse buying. Cognitive assimilation mediates the relationship between streamer attractiveness and information quality on impulse buying. Between millennial generation - generation z there is no difference in impulse buying.